2016
DOI: 10.21802/gmj.2016.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperglycemia on the Excretory Ducts of the Submandibular Gland (Histologic Study)

Abstract: The paper highlights the peculiarities of histological changes in different subdivisions of the intralobular duct of the submandibular gland in rats in case of experimental hyperglycemia. Materials and methods. The study included 40 male Wistar rats weighing 230 to 250g. Experimental hyperglycemia was induced by a single intraperitoneal administration of streptozotocin. Biochemical and morphological investigations were conducted; the morphometric analysis was carried out. Results. Since the 28th day of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In the present study, flattening of ID cells in diabetic subgroup IIB and SD cells in both diabetic subgroups was detected, this result is in agreement to [26] as epithelial cell height in the ID and SD of diabetic submandibular SG begins to change due to the direct effect of hyperglycemia and oxidative stress and indirect due to diabetic microangiopathy. SD of both diabetic subgroups showed loss of basal striation, this result agrees with [27] and they accredited this due to degeneration of mitochondria which appeared swollen with loss of cristae.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, flattening of ID cells in diabetic subgroup IIB and SD cells in both diabetic subgroups was detected, this result is in agreement to [26] as epithelial cell height in the ID and SD of diabetic submandibular SG begins to change due to the direct effect of hyperglycemia and oxidative stress and indirect due to diabetic microangiopathy. SD of both diabetic subgroups showed loss of basal striation, this result agrees with [27] and they accredited this due to degeneration of mitochondria which appeared swollen with loss of cristae.…”
Section: Discussionsupporting
confidence: 91%
“…Sandberg GE et al (1970) have reported that oral dryness symptom of type 2 diabetic patients is significantly higher than that in normal people [6]. In addition, it is reported that a study showing morphological changes in the intralobular duct of the salivary gland due to hyperglycemia has been reported [9]. It was reported that function of salivary glands and salivation decreased due to apoptosis of salivary glands cells caused by head and neck radiation therapy [10] [11].…”
Section: Introductionmentioning
confidence: 99%